A secondary analysis using individual patient data of two pragmatic cluster-randomized control trials evaluating 3 monthly and 6 monthly community-based multimonth dispensing of antiretroviral treatment in Southern Africa - Lopes, John (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.